Energy Intake, PUFA, Vitamin E, Vitamin B1, and Vitamin B6 with Hemoglobin Levels in Chronic Kidney Disease Patients - Luh Desi Puspareni; Rani Triani; Taufiq Firdaus Algifari Atmaja (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Chronic kidney disease (CKD) is a structural or functional kidney disorder that lasts for three months or longer despite poor health. Patients with kidney disease are at risk of developing anemia, the primary etiology of which is decreased erythropoietin. Energy intake, polyunsaturated fatty acids (PUFA), vitamin E, vitamin B1, and vitamin B6 play a role in erythropoiesis. The purpose of this study was to analyze the association between energy intake, PUFA, vitamin E, vitamin B1, and vitamin B6 with Hb levels in CKD patients undergoing hemodialysis at Ciamis Regional General Hospital. This study used a cross-sectional design. The sampling technique in this study used non-probability sampling with quota sampling with a sample size of 74 subjects. Energy intake, PUFA, vitamin E, vitamin B1, and vitamin B6 were obtained through 3 x 24-hour non-consecutive food recalls. Data on subjects' hemoglobin levels used pre-hemodialysis hemoglobin levels obtained from subjects' medical records. Bivariate analysis used the Spearman-Rank correlation test. The results of the study showed that there was an association between energy intake (p-value = 0.000; ρ = 0.534), PUFA (p-value = 0.002; ρ = 0.367), vitamin E (p-value = 0.001; ρ = 0.370), vitamin B1 (p-value = 0.001; ρ = 0.370), and vitamin B6 (p-value = <0.001; ρ = 0.471) with Hb levels. It was concluded that energy intake, PUFA, vitamin E, vitamin B1, and vitamin B6 with Hb levels in CKD patients undergoing hemodialysis. Adequate energy intake and a diet rich in PUFA, vitamin E, vitamin B1, and vitamin B6 ciuld help prevent anemia in CKD patients undergoing hemodialysis.